(untitled) - B.M.A.S. Anaconda Bangkara (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research is intended to obtain patterns or models of organizational communication in relation to 'knowledge share'. This research was conducted at a MNC manufacturing company in the Jababeka area, Cikarang, Bekasi, West Java Province, Indonesia. This research applies inductive research, case study, participant observation, to 12 informants, from the year of 2014 to 2017, then reconfirmed in 2019 and early 2020 before the covid-19 pandemic. The analysis tools used are Word Counts, Constant Comparison Analysis, Classical Content Analysis, Domain Analysis, and Taxonomic Analysis., With the help of NVivo 10 software. The results of this study indicate that employees prefer a familiar and informal atmosphere and prefer to communicate verbally in order to do 'knowledge share'.